MULTICULTURAL VALUES REPRESENTATION IN AN INDONESIAN EFL TEXTBOOK - Roviandini, Eka Yuniar; Suharjito, Bambang; Fitriani, Ika (UC Journal: ELT, Linguistics and Literature Journal, 2025)
Cultural imbalance in English Language Teaching (ELT) textbooks remains a major concern in Indonesia’s EFL contexts. Many government-endorsed ELT textbooks often emphasize local culture while neglecting global perspectives, which can hinder the development of students' Intercultural Communicative Competence (ICC). To address this issue, this study examines the representation of multicultural values in Pathway to English for tenth-graders, a non-government-endorsed ELT textbook. Using Moran's (2001) five cultural dimensions and Fairclough’s (1995) Critical Discourse Analysis (CDA) framework, the findings reveal that the textbook reflects three values: appreciating other people’s cultural products (AOPCP), respecting other people’s communities (ROPC), and appreciating other people’s practices (AOPP). However, the textbook lacks representations of cultural perspectives and figures. While it introduces international cultures, the content focuses heavily on cultural products, limiting opportunities to fully develop students' ICC. These results suggest that more balanced and comprehensive cultural content is essential in ELT textbooks to support the holistic development of students' ICC in a globalized world.